Enhanced corrosion protection by Al surface immobilization of in-situ grown layered double hydroxide films co-intercalated with inhibitors and low surface energy species. (March 2020) - Cao, Yanhui; Zheng, Dajiang; Luo, Jingsong; Zhang, Fan; Wang, Cheng; Dong, Shigang; Ma, Yanlong; Liang, Zhaoyuan; Lin, Changjian
Highlights: A novel ZnAl-LDH film co-intercalated with vanadates and laurates was fabricated. The long-term corrosion properties of ZnAl-LDH-VOx-La was evaluated. The long-term anion-exchange properties of ZnAl-LDH-VOx-La was evaluated. The protection mechanism is proposed in terms of synergistic effect. Abstract: In this work, a novel in-situ grown layered double hydroxide (LDH) film co-intercalated with inhibitors (vanadates) and low surface energy substance (laurates) was immobilized on Al substrates. A long-term monitoring of electrochemical impedance spectra (EIS) of the various samples in 3.5 wt.% NaCl solution demonstrated the synergetic protection of the intercalated two functional species. Meanwhile, the X-ray diffraction (XRD) result of the samples after immersion in NaCl solution for a long time presented the anion-exchange process between vanadates/laurates and chlorides. The synergetic effect of the two species loaded film significantly contributed to the enhanced long-term corrosion protection of aluminum.